Organizational cynicism and employee performance: evidence from a Sri Lankan audit sector - Panchali, Jayasekara; Seneviratne, S. M. (Annals of Management and Organization Research, 2019)
Purpose: This study examined the relationship between organizational cynicism and employee performance at diverse hierarchical levels in big four audit firms in Sri Lanka. Research methodology: By adopting quantitative research methodology, questionnaires were used as a primary data collection method from audit trainees, audit supervisors, and audit managers in big 4 audit firms in Sri Lanka. This was conducted by deploying a convenient sampling technique, and regression models are used by applying SPSS. Results: The study found a significant negative relationship between organizational cynicism and employee performance at audit firms and that each dimension of organizational cynicism. Limitations: Organizational cynicism was analyzed based on employee perception, although there are other influencing factors for organizational cynicism. Contribution: This study's findings are expected to support audit supervisors in avoiding the discovered negative effect instead by lessening the degree of psychological contract violation and organizational politics. Keywords: Organizational cynicism, Employee performance, Audit firms, Affective cynicism, Cognitive cynicism, Behavioral cynicism